Analisis Strategi E-Business Pada Bandung Smart City - putri dina mardika (LPPM, 2018)
Abstract. The design of a city through the use of information technology makes it a necessity, not just for the lifestyle in terms of communicating the accuracy and usefulness of the scope of urban planning. It leads to a term that is smart city. Problems encountered in relation to smart city include the lack of optimal government services, lack of community to participate in support of the Smart City concept movement, and human resource competence has not been optimal. One of the city concept city concept is the city of Bandung, which has an integrated network covering aspects of Smart Government, Smart Education, Smart Transportation, Smart Health, Smart Infrastructural, Smart Social, Smart Environment, Bandung Technopolis so that make the city of Bandung the better. Using SWOT method, which analyzed from the aspect of Resilience or Strength, Weakness, Opportunities and Risks in Knowing Strategy can make Bandung have smart city image. The conclusions generated from the results of strategy analysis that is with the existence of Human Resources that qualified to maintain integrated product or application which then disseminated to the public. Thus, Bandung becomes a smart city that inspires other cities in Indonesia.Keywords: Smart City, Bandung Smart City, SWOT Analysis